Rooie Vlinder info : maandelijks informatieschrift. - De Rooie Vlinder (Antwerpen : Rooie Vlinderkollektief, 1977)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Keizerstraat 38, 2000 Antwerpen ; Visserij 132, 9000 Gent
Laatse n° 05(1981)sep.-okt.
Nederlands
Periodiek